KEMAMPUAN MATEMATIKA SISWA KELAS VIII SMP DI DAERAH ISTIMEWA YOGYAKARTA DALAM MENYELESAIKAN SOAL MODEL TIMSS - Jailani Jailani; Nidya Ferry Wulandari (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2017)
This research describes 8th grade students’ ability in solving TIMSS-model questions. Samples were 400 students from 15 junior high schools (SMP) in Yogyakarta. Students were subjected to a written test with 45 TIMSS-model questions exploring both content and cognitive domain. Students’ ability in solving the given questions was subsequently analyzed descriptively. Results showed that 48% students were categorized in a low or very low category and only 25% students were in a high or very high category. Students particularly faced difficulty in solving algebra, geometry, data and probability questions. In terms of cognitive domain, students have a low ability in solving reasoning questions. Comparison between results from this present study with results from TIMSS 2011 showed that students’ ability in this present study was far better than TIMSS 2011 results for Indonesia and slightly higher than TIMSS 2011’s international average. Implications and suggestions for mathematics education program improvement in Indonesia are discussed.AbstrakPenelitian ini mendeskripsikan kemampuan siswa kelas 8 dalam menyelesaikan soal-soal model TIMSS. Sampel adalah 400 siswa dari 15 Sekolah Menengah Pertama (SMP) di Yogyakarta. Setiap siswa diberikan soal ujian tertulis dengan 45 soal model TIMSS yang mengeksplorasi baik domain konten maupun kognitif. Kemampuan siswa dalam menyelesaikan soal-soal yang diberikan kemudian dianalisis secara deskriptif. Hasil menunjukkan bahwa 48% siswa dikategorikan dalam kategori rendah atau sangat rendah dan hanya 25% siswa yang dikategorikan dalam kategori tinggi ataupun sangat tinggi. Siswa terutama mengalamai kesulitan dalam menyelesaikan soal-soal aljabar, geometri, data dan peluang. Dalam hal domain kognitif, siswa memiliki kemampuan yang rendah dalam menyelesaikan soal-soal penalaran. Perbandingan antara hasil pada penelitian ini dengan hasil TIMSS tahun 2011 menunjukkan bahwa kemampuan siswa dalam penelitian ini jauh lebih baik dengan hasil TIMSS tahun 2011 untuk Indonesia dan sedikit lebih tinggi dibandingkan rata-rata internasional TIMSS 2011. Implikasi dan saran untuk perbaikan program pendidikan matematika di Indonesia kemudian didiskusikan.